Sexual dimorphism in inorganic mercury toxicokinetics and the attendant lipotoxic and non-lipotoxic dyslipidemia in the rat - A.D. Wusu; O.O. Ogunrinola; O.K. Afolabi; E.O. Abam; D.O. Babayemi; O.A. Dosumu; O.B. Onunkwor; E.A. Balogun; O.O. Odukoya; O. Ademuyiwa (Biochemistry and Biophysics Reports, 2021)
The influence of variability in the biology of living organisms is poorly appreciated in toxicology. However, multiple lines of evidence indicate that sex-differences modulate toxicokinetics and toxicodynamics from cellular/molecular to whole animal levels resulting in different toxic responses of living organisms to xenobiotics exposure. In order to investigate the influence of sex in inorganic mercury (Hg) exposure, male and female Wistar rats were exposed to 0.5, 1.0 and 1.5 mg Hg/kg body weight orally as HgCl2 twice a week for 12 weeks. Higher Hg levels in the females (except heart) as compared to males were observed in the animals. At the highest dose of inorganic Hg, female renal Hg content was 3.3 times higher than that of the males. Mixed sexual dimorphism characterised circulating-lipid- and organ-lipid lipotoxic and non-lipotoxic dyslipidemia. The highest dose of inorganic Hg, induced hypercholesterolemia in the males as opposed to hypocholesterolemia in the female. Plasma and erythrocyte free fatty acids increased in both sexes, although the increase was more pronounced in the male. Reverse cholesterol transport was inhibited in the male at the highest dose of Hg, whereas female HDL became enriched with cholesterol. Female erythrocytes had all their lipids increased, whereas only male erythrocyte triglyceride increased. Brain cholesterol and phospholipids, and splenic phospholipids were depleted in both sexes. Our findings indicate that inorganic Hg exposure appears to affect Hg and lipid kinetics differently in both sexes, thus underscoring the need to develop sex-tailored approaches in the treatment of metal toxicosis and its metabolic outcomes.